Comparison of Predictability Using Barrett Universal II and SRK/T Formulas according to Keratometry - Kei Iijima; Kazutaka Kamiya; Yoshihiko Iida; Nobuyuki Shoji (Journal of Ophthalmology)
Purpose. To compare the predictability of intraocular lens (IOL) power calculation using the Barrett Universal II and the SRK/T formulas, according to the keratometry. Methods. We retrospectively reviewed the clinical charts of 335 consecutive eyes undergoing standard cataract surgery. IOL power calculations were performed using the Barrett Universal II and the SRK/T formulas. We compared the prediction error, the absolute error, and the percentages within ±0.25, ±0.5, and ±1.0 D of the targeted refraction, 1 month postoperatively, and also investigated the relationship of these outcomes with the keratometric readings, using the two formulas. Results. The prediction error using the SRK/T formula was significantly more myopic than that using the Barrett Universal II formula (the paired t-test, p<0.001). The absolute error using the SRK/T formula was significantly larger than that using the Barrett Universal II formula (p=0.006). We found a significant correlation between the prediction error and the keratometric readings using the SRK/T formula (Pearson correlation coefficient, r = −0.522, p<0.001), but there was no significant correlation between them using the Barrett Universal II formula (r = −0.031, p=0.576). Conclusions. The Barrett Universal II formula provides a better predictability of IOL power calculation and is less susceptible to the effect of the corneal shape, than the SRK/T formula. The Barrett Universal formula, instead of the SRK/T formula, may be clinically helpful for improving the refractive accuracy, especially in eyes with steep or flat corneas.